Romanticism, origins, and the history of heredity - Lehleiter, Christine (New studies in the age of Goethe., 2014)
Examining novels, studies on plant hybridization, treatises on animal breeding, and collections of anatomical monstrosities, Origins Matter delineates how romantic authors imagined the ramifications of emerging notions of heredity for the conceptualization of selfhood